2020
DOI: 10.20473/jps.v9i2.19123
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training Program for Autism Spectrum Disorder During The Covid-19 Pandemic Period in Indonesia

Abstract: Autism Spectrum Disorder (ASD) is a pervasive developmental disorder that shows difficulties in communication, social interaction, behavior, interests and activities that are limited and repetitive. The prevalence of ASD also continues to increase worldwide, followed by an increase in the need for early intervention in ASD children. The limited services available make early intervention a challenge in itself. The long Covid-19 pandemic has resulted in limited therapy, because therapy in treatment service facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The Autism Alliance of Michigan offers an autistic care program in their homes, but most parents are worried that the waiter will bring COVID-19 into their home, so most parents do not need it. Ina et al's research found that the parent training program positively impacted children and their parents or families 12 . In addition, it is helpful to increase knowledge and insight about the individual child, enable the incorporation of therapy into the child's environment and facilitate generalization of the skills learned.…”
Section: Discussionmentioning
confidence: 99%
“…The Autism Alliance of Michigan offers an autistic care program in their homes, but most parents are worried that the waiter will bring COVID-19 into their home, so most parents do not need it. Ina et al's research found that the parent training program positively impacted children and their parents or families 12 . In addition, it is helpful to increase knowledge and insight about the individual child, enable the incorporation of therapy into the child's environment and facilitate generalization of the skills learned.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention to this student was discontinued due to the dynamics of the pandemic and subsequently it was investigated whether this led to negative effects on the course of therapeutic intervention. As it was found, just one and a half months of interruption was enough for the previous treatment conquests to have been lost [55]. Attempts to implement online interventions have been carried out [56], although it is doubtful if such interventions can have an equal impact with face-toface interventions, especially in autism, where interventions based on technology are integrated to a child's physical environment.…”
Section: The Effect On Students With Autismmentioning
confidence: 99%
“…Although, she had found how to pronounce the English word, she still had difficulty to pronounce it. As Ardiyani, et al, (2020) said, parents can also take the role of coach or therapist in various interventions.…”
Section: Online Learningmentioning
confidence: 99%